Kontekstualisasi Hadis Jibril terhadap Fenomena Kekerasan Anak pada Orang Tua - Eva Marpuah; Suci Amalia (Tadabbur: Jurnal Integrasi Keilmuan, 2022)
The number of cases of child abuse against parents today urges to be investigated and found a solution. Because it is lamentable and not in accordance with religious values also contrary to human rights. This paper, using the library method, will summarize several acts of child violence against parents from the last 3 years as evidence that this action is not a fabrication. The conclusion that emerges in this paper is that the prophet Muhammad PBUH in his hadith has predicted this phenomenon. Through the Hadith of Jibril, it can also be seen why acts of violence against children occur against their parents. It also can be seen that as time progresses, human morals decrease. In addition to predictions through Jibril's hadith, there are several other causes of child violence against parents such as wrong parenting and environmental factors that are not good.